(3cJGH GdcGaj aj Yde GdMSGHs - (3CHh aNQ GdOjf eMeO Hf GdMSf, GdMGSH GdcQNjs
(3ChdgG (B:s
(3bGd bO WGd HGdeNJUQ GdPi SCdJfi JUfjag HYV GdCNhGf HGH VQH GdUMGM s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg hKdK TF jYOd eGFI hKdKI Efg NQL KdGKI hKdGKhf OQgekG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeS YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1377s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs